Literature review: Considerations in undertaking focus group research with culturally and linguistically diverse groups - Halcomb, E.; Gholizedah, L.; DiGiacomo, Michelle; Phillips, J.; Davidson, Patricia (Blackwell Publishing, 2007)
Aims: This integrated literature review seeks to identify the key considerations in conducting focus groups and discusses the specific considerations for research with culturally and linguistically diverse groups. Background: The focus group method is a technique of group interview that generates data through the opinions expressed by participants. Focus groups have become an increasingly popular method of data collection in health care research. Although focus groups have been used extensively with Western populations, they are a particularly useful tool for engaging culturally and linguistically diverse populations. The success of focus groups in this context is dependent upon the cultural competence of the research team and the research questions. Methods: The electronic databases Medline, CINAHL, Embase, Psychlit and the Internet using the Google Scholar search engine were explored using the search terms ‘focus group’, ‘cultural sensitivity’, ‘transcultural nursing’, ‘transcultural care’, ‘cultural diversity’ and ‘ethnic groups’. Hand searching of reference lists and relevant journals was also undertaken. English language articles were selected for the review if they discussed the following issues: (1) methodological implications of the focus group method; (2) strengths and limitations of the focus group method; (3) recommendations for researchers and (4) use of the focus group in culturally and linguistically diverse groups. Conclusions were drawn from each of the articles and consensus regarding a summary of recommendations was derived from a minimum of two authors. Results: Findings from this review revealed several key issues involving focus group implementation including recruitment, sample size, data collection, data analysis and use within multicultural populations. Strengths and limitations of the focus group method were also identified. Conclusions: Focus groups are a useful tool to expand existing knowledge about service provision and identify consumer needs that will assist in the development of future intervention programs, particularly within multicultural populations. Careful planning related to methodological and pragmatic issues are critical in deriving effective data and protecting participants. Relevance to clinical practice: Focus groups can facilitate increased understanding of perspectives of culturally and linguistically diverse groups and thereby shape clinical practice to better meet the needs of these groups.